Philippine predatory mites of the family cunaxidae (Acari). 5. Genera Neoscirula Den Heyer, Parabonzia Smiley and Orangescirula Bu & Li - Corpuz-Raros, L.A. (1996)
Philippine predatory cunaxid mites of the genera Neoscirula Den Heyer, Parabonzia Smiley and Orangescirula Bu & Li are treated taxonomically in this paper. They include seven, three and one species, respectively. Seven new species are described as new to science, namely, Neoscirula abraensis, N. aspirasi, N. imperata, N. makilingica, N. putinglupa, Parabonzia mindanensis and Orangescirula filipina. Three species are recorded as new for the Philippines, namely, N. luxtoni Smiley, N. ogawai (Shiba) and P. marthae (Den Heyer). Keys to species of Neoscirula and Parabonzia are given based on females. Each species is provided with descriptions, illustrations and distributional data.
Keywords: Mites